Pembentukan Posyandu Remaja untuk memantau Kesehatan Reproduksi dan Komunikasi Informasi Edukasi Gizi bagi Remaja di SMK 4 Kendal - Sri Rahayu Rubyanto; Marhaeni DS; Sri Sayekti; Agus Sudrajat (Universitas Muhammadiyah Klaten, 2024)
One of the public health programs that is very important for the development and health of Indonesian society is Posyandu which is aimed at improving the health of adolescents in urban and rural areas. It is hoped that the youth Posyandu will become a community forum that facilitates teenagers in understanding their health problems, expanding the reach of the PKPR Community Health Center in providing promotive and preventive services to target teenagers, especially teenagers in the regions. Based on this problem, our community service team intends to hold a socialization for youth posyandu at SMK Negeri 4 Kedal which will be held in May – June 2024. The method of implementation, discussion, socialization of reproductive health and nutrition material for teenagers includes a tutorial on how to use Z-scrore which is useful as a monitor growth and development development for adolescents. Results: teenagers at SMK Negeri 4 Kendal formed a youth posyandu which was held once a month and coordinated with the Brangsong health center in youth posyandu activities. The conclusion is that the role of the UKS and PMR supervisors will be to carry out youth posyandu regularly in coordination with the Bransong 2 Kendal community health center.